2010
DOI: 10.1523/jneurosci.3021-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Extrasynaptic, But Not Synaptic, NMDA Receptors Modifies Amyloid Precursor Protein Expression Pattern and Increases Amyloid-β Production

Abstract: Calcium is a key mediator controlling essential neuronal functions depending on electrical activity. Altered neuronal calcium homeostasis affects metabolism of amyloid precursor protein (APP), leading to increased production of ␤-amyloid (A␤), and contributing to the initiation of Alzheimer's disease (AD). A linkage between excessive glutamate receptor activation and neuronal A␤ release was established, and recent reports suggest that synaptic and extrasynaptic NMDA receptor (NMDAR) activation may have distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 67 publications
(97 reference statements)
3
149
0
1
Order By: Relevance
“…Although this paradigm first was demonstrated for ischemic brain disease, accumulating evidence suggests that it also is true for neurodegenerative disorders involving protein misfolding, such as Huntington disease (3,4) and AD (7,8,59,60). Additionally, linking this dichotomy of eNMDAR vs. sNMDAR activation to synaptic integrity, we and others previously have shown that low levels of glutamate or endogenous synaptic activity may enhance dendritic spine growth (61,62).…”
Section: Discussionmentioning
confidence: 90%
“…Although this paradigm first was demonstrated for ischemic brain disease, accumulating evidence suggests that it also is true for neurodegenerative disorders involving protein misfolding, such as Huntington disease (3,4) and AD (7,8,59,60). Additionally, linking this dichotomy of eNMDAR vs. sNMDAR activation to synaptic integrity, we and others previously have shown that low levels of glutamate or endogenous synaptic activity may enhance dendritic spine growth (61,62).…”
Section: Discussionmentioning
confidence: 90%
“…In the same way, this dichotomous nature of NMDAR signaling has also been outlined in the fi eld of neurological disorders (Hardingham and Bading , 2010 ). Recently, our group provided data suggesting that perturbations in the balance between synaptic and extrasynaptic NMDAR activity could increase neuronal A β production, contributing to the pathogenesis of AD (Bordji et al , 2010 ).…”
Section: Introductionmentioning
confidence: 54%
“…In a recent study, we have evidenced a direct relationship between prolonged extrasynaptic NMDAR activation and neuronal A β production (Bordji et al , 2010 ). The release of A β was preceded by the neuronal induction of KPI-APPs, isoforms exhibiting an important amyloidogenic potential.…”
Section: Targeting Extrasynaptic Nmdars To Lower a β Peptide: Interesmentioning
confidence: 88%
See 1 more Smart Citation
“…In mouse models of AD and HD, neurons derived from affected brain regions have defective LTP 25,26 . Furthermore, the activation of extrasynaptic NMDARs in a mouse model of AD promotes ß-secretase cleavage of APP, which results in increased levels of Aβ that are directly correlated with the severity of the cognitive deficit 27 . The presence of Aβ oligomers, early intermediates in the Aβ aggregation pathway, has in turn been associated with increased activation of extrasynaptic NMDARs, which could cause a feedback loop leading to synaptic dysfunction 28 .…”
Section: Aberrant Extrasynaptic Nmda Receptor Activity In Hd and Admentioning
confidence: 99%